Varied response of western Pacific hydrology to climate forcings over the last glacial period - Stacy A, Carolin; Kim M, Cobb; Jess F, Adkins; Brian, Clark; Jessica L, Conroy; Syria, Lejau; Jenny, Malang; Andrew A, Tuen (American Association for the Advancement of Science, 2013)
Atmospheric deep convection in the west Pacific plays a key role in the global heat and moisture budgets, yet its response to orbital and abrupt climate change events is poorly resolved. Here, we present four absolutely dated, overlapping stalagmite oxygen isotopic records from northern Borneo that span most of the last glacial cycle. The records suggest that northern Borneo’s hydroclimate shifted in phase with precessional forcing but was only weakly affected by glacial-interglacial changes in global climate boundary conditions. Regional convection likely decreased during Heinrich events, but other Northern Hemisphere abrupt climate change events are notably absent. The new records suggest that the deep tropical Pacific hydroclimate variability may have played an important role in shaping the global response to the largest abrupt climate change events.